2014
DOI: 10.1523/jneurosci.4646-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mouse Lines Subdivide External Segment of the Globus Pallidus (GPe) Neurons and Reveal Distinct GPe Output Pathways

Abstract: Cell-type diversity in the brain enables the assembly of complex neural circuits, whose organization and patterns of activity give rise to brain function. However, the identification of distinct neuronal populations within a given brain region is often complicated by a lack of objective criteria to distinguish one neuronal population from another. In the external segment of the globus pallidus (GPe), neuronal populations have been defined using molecular, anatomical, and electrophysiological criteria, but thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
248
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(282 citation statements)
references
References 98 publications
25
248
2
Order By: Relevance
“…One candidate is the external segment of the globus pallidus. This structure sends GABAergic projections to both MSNs and FSIs in the dorsal striatum (Bevan et al, 1998;Mallet et al, 2012;Mastro et al, 2014) and these projections express pre-proenkephalin (Mallet et al, 2012). Given that the variability in the induction of EtOH-LTD at the FSI-MSN synapse is not explained by differences in FSI-MSN D and FSI-MSN ID pathways, and that DPDPE application consistently induces FSI-MSN synaptic depression, the heterogeneous expression of FSI-MSN EtOH-LTD may be due to the variability in the EtOH-induced release of the endogenous DOR agonist.…”
Section: Discussionmentioning
confidence: 99%
“…One candidate is the external segment of the globus pallidus. This structure sends GABAergic projections to both MSNs and FSIs in the dorsal striatum (Bevan et al, 1998;Mallet et al, 2012;Mastro et al, 2014) and these projections express pre-proenkephalin (Mallet et al, 2012). Given that the variability in the induction of EtOH-LTD at the FSI-MSN synapse is not explained by differences in FSI-MSN D and FSI-MSN ID pathways, and that DPDPE application consistently induces FSI-MSN synaptic depression, the heterogeneous expression of FSI-MSN EtOH-LTD may be due to the variability in the EtOH-induced release of the endogenous DOR agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, we did not consider heterogeneity within the GPe. Recent studies have demonstrated functional as well as structural dichotomy in the GPe [Mallet et al, 2012, Mastro et al, 2014, Abdi et al, 2015. As gap junctions between cortical interneurons typically couple cells of the same type (see above), it is possible that also pallidal gap junctions couple only within one population, or within both populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has become apparent that GPe also densely inhibits striatum [Fujiyama et al, 2015], building the basis for a feedback loop between these two nuclei. Moreover, we modeled only one GPe population, although it is known that several types of GPe neurons, differing in both structure and function, exist [Mallet et al, 2012, Mastro et al, 2014, Abdi et al, 2015. Despite all this neglected detail and heterogeneity, we suggest that our model has biological relevance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations